Experimental design of steel bearings and ceramic bearings to find efficient energy consumption - Suhariyanto Suhariyanto; Heru Mirmanto; Azlan Arifin Khan; Rohmadoni Rohmadoni (International Journal of Industrial Optimization, 2023)
A bearing is a vital machine component that supports shafts, enabling smooth rotation and minimizing friction. The level of friction is determined by the coefficient of friction, which varies based on the bearing material. In this study, we evaluated two types of bearings: steel and ceramic, with the aim of identifying the one with the lowest frictional force and, consequently, the least input power required. To conduct a comprehensive comparison, we performed comparative tests on the Nogogeni Evo V vehicle, analyzing the energy consumption impact of both steel and ceramic bearings. The tests involved measuring the input power of each bearing type at various throttle openings, ranging from 10% to 100%. The results revealed that ceramic bearings exhibited superior energy efficiency compared to their steel counterparts. At all throttle openings, the ceramic bearings consistently demanded lower input power, indicating their higher efficiency. For instance, at 100% throttle opening, the input power for steel bearings was 17,939 watts, while ceramic bearings required only 17,290 watts, representing a 3.6% reduction. Moreover, ceramic bearings achieved higher rotation speeds, with the ceramic bearing rotating at 598 rpm, a 3.5% increase compared to the steel bearing's 577 rpm. Based on these findings, it can be concluded that the implementation of ceramic bearings would significantly enhance the energy efficiency of the Mobil Nogogeni Evo V electric motor. Therefore, for improved performance and reduced energy consumption, we recommend the incorporation of ceramic bearings in the vehicle's design.